Distributed Leadership and Teacher Turnover Intention: The Mediating Roles of Teacher Efficacy and Work Engagement and the Moderating Role of Interpersonal Trust (IJORER : International Journal of Recent Educational Research, 2026)
Objective: Teacher turnover intention remains a critical challenge in vocational education, particularly in emerging economies where teacher retention is essential for maintaining instructional quality and sustainable school development. This study examines the effect of distributed leadership on teacher turnoverintention, mediated by teacher efficacy and work engagement and moderated by interpersonaltrust. Method: This study utilized a quantitative explanatory survey design. Data were obtained from 250 teachers in private vocational high schools in Surakarta, Indonesia, using cluster sampling. The proposed mediated–moderated model was assessed using Partial Least Squares Structural Equation Modeling (PLS-SEM) which draws on Conservation of Resources (COR) Theory. Results: The findings demonstrate that distributed leadership has a significant positive effect on teacher efficacy and work engagement. Both variables significantly reduce teacher turnover intention, with work engagement emerging as the strongest predictor. Teacher efficacy also significantly mediates the relationship between distributed leadership and work engagement. Furthermore, interpersonal trust negatively moderates the relationship between distributed leadership and teacher efficacy, indicating a resource saturation effect in high-trust environments. Novelty: Based on Conservation of Resources (COR) Theory, this study offers new theoretical insight by demonstrating that leadership resources do not operate linearly. Using a moderated-mediation model, the findings reveal a resource saturation effect in which high interpersonal trust weakens the marginal impact of distributed leadership on teacher efficacy. This extends leadership research by empirically identifying the boundary conditions of distributed leadership and refining COR Theory within vocational education settings.